Kerion Barbae with Bacterial Superinfection Presenting as a Rapidly Growing Beard Mass: A Diagnostic Dilemma in a Resource-Limited Setting - Sitaula, Sabina; Bastola, Ashok; Sitaula, Saroj; Shrestha, Yusha; Dhakal, Shishan (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Tinea barbae is a rare dermatophyte infection of the beard and mustache region, often seen in agricultural workers due to zoonotic transmission. Its inflammatory form, kerion barbae, can mimic bacterial infections, granulomatous dermatoses, or even malignancy, leading to misdiagnosis. We report a case of a 55-year-old male farmer from rural Nepal who presented with a one-month history of nodulo-ulcerative and pustular lesions over the chin and beard area. Clinical examination revealed an indurated plaque with purulent discharge, crusting, and easily pluckable beard hairs. Pus culture grew Staphylococcus aureus, while the potassium hydroxide mount and periodic acid–Schiff stain were negative for fungal elements, whereas fungal culture was unavailable. Despite antibiotic therapy, only partial improvement was achieved. Considering kerion barbae, oral itraconazole was initiated, resulting in rapid clinical improvement and complete resolution within four weeks. This case highlights the possible misdiagnosis of kerion barbae, particularly when complicated by bacterial superinfection, as false-negative KOH and PAS results are not uncommon. Kerion barbae should be considered in rapidly enlarging nodulo-ulcerative beard lesions unresponsive to antibiotics, especially in resource-limited settings. A therapeutic trial of antifungal therapy is justified to avoid misdiagnosis and prevent sequelae such as scarring and alopecia.